Community Service of Competitiveness Improvement of Elo River Rafting Tourism Magelang Regency - Ahmad Muhlisin; Siswanto Siswanto; Moch Malik Al Firdaus (LPPM IKIP PGRI Pontianak, 2021)
Local and foreign tourists visit potential in Elo River rafting tourism evinces anincrease every year. Therefore, it is important to improve management andhuman resource skills. This community service (Pengabdian KepadaMasyarakat/PKM) aims to improve Elo River rafting tourism competitivenessthrough the development of integrated website, Statutes and Bylaws (AD/ART),Standard Operating Procedures (SOP), and enhancement of Englishcommunication skill. The service methods are applied using direct methods frompreparation, implementation, and evaluation. The results of activitiesimplementation indicate that the activities are well implemented in accordancewith the pre-determined targets and outcomes. The activities executed provide anillustration that it produces added values; thus it improves the competitiveness ofElo River operator association. Follow-up efforts of the implemented programsinclude cooperation between Universitas Tidar and the Elo River raftingassociation in the efforts of competitiveness improvement in terms of EnglishSkills and the administration of competence test for tour guides.